Community development approaches and methods: Implications for community development practice and research. Issue 5 (20th October 2018) - Quimbo, Maria Ana T.; Perez, John Erinorio M.; Tan, Francisca O.
ABSTRACT: This study highlights an analysis of the evolution and development of various community development approaches and methods. This includes a contextual review and qualitative meta-analysis of empirical studies dealing with approaches and methods in community development spanning five decades of Philippine research studies and cases. A total of 217 studies in community development conducted by students in Philippine universities were reviewed for this study. Overall, our review documents an increase in the number of community development research and studies in the Philippines. It is noteworthy that through the five decades of Philippine community development experience, there was a steady and persistent use of community-based and participatory approaches to development work. Community education and community organizing remained the popular strategies for successful development intervention. The study recommends an integrated model of community development practice in the Philippines useful for both researchers and practitioners.